Personal Ambitions, Expertise and Parties' Control: Understanding Committee Assignment in the Italian Chamber of Deputies. Issue 1 (19th March 2018) - Giannetti, Daniela; Pedrazzani, Andrea; Pinto, Luca
Abstract: In this study, we look at committee assignment by focusing on the extent to which MPs' desires to become members of certain committees are fulfilled. Our theoretical argument is based on the assumption that legislators pursue individual goals, which interact with party leaders' ones. To test our hypotheses, we use original survey data on elected candidates to the Italian Parliament that were collected immediately after the 2013 general election. Our main findings highlight that individual preferences driven by distributive interests are more likely to be accommodated in the case of legislators who are close to their party in ideological terms. On the contrary, ideological proximity to the party does not seem to affect committee assignment when MPs' preferences are driven by expertise-based motivations.